Conceptual framework for the implementation of interventions in the construction industry - van der Molen, Henk F.; Sluiter, Judith K.; Hulshof, Carel TJ; Vink, Peter; van Duivenbooden, Cor; Frings-Dresen, Monique HW (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'The objective of this study was to explore the necessary steps to define the implementation of interventions aimed at reducing physical work demands due to manual materials handling in the construction industry. ' ' METHODS ': 'A theoretical structured framework of six steps is outlined as a method for developing the implementation of interventions. In this framework, both the proposal for implementing the intervention measures and the context analysis are conditional. ' ' RESULTS ': 'Application of the framework in the development of the implementation of interventions to reduce the physical work demands for bricklayers and bricklayers’ assistants has been presented. ' ' CONCLUSIONS ': 'The framework was found appropriate for defining implementation strategies and (ergonomic) measures in the construction industry.
Keywords: conceptual framework; construction industry; implementation; intervention; manual materials handling; method